Nuevos registros de crinoideos (Echinodermata: Crinoidea) en el talud continental de Chile - Catalán, Jennifer; Merino-Yunnissi, Catalina; Martínez, Andrea; Sellanes, Javie; Ibáñez, Christian M. (Revista de Biología Marina y Oceanografía, 2020)
The presence of Solanometra antarctica has been reported in the continental slope of central Chile, however, some studies suggest that this species could have been confused with Florometra magellanica. In this study, 11 crinoid specimens obtained in the continental slope of Central Chile were analyzed and compared with other specimens previously collected in that same region and catalogued as Florometra magellanica. The morphological and meristic characteristics confirm that the crinoids collected in Central Chile, off Concepción and Los Vilos, correspond to Florometra magellanica.